1973
DOI: 10.1103/physrevlett.30.829
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Collisionless Sound in Normal and Extraordinary Phases of LiquidHe3below 3 mK

Abstract: In this Letter we present measurements of the attenuation and velocity of ultrasound in liquid 3 He at temperatures below 3 raK and at various pressures" In this temperature region and in the presence of solid 3 He, two new phases with extraordinary NMR properties were discovered by Osheroff et al. 1 In this same temperature region Webb et al. 2 observed a second-order phase transition, a discontinuity but not a divergence in the specific heat, over a wide range of pressure in liquid 3 He. This phase transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
27
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(28 citation statements)
references
References 7 publications
1
27
0
Order By: Relevance
“…We have identified the appearance of superfluidity as the temperature where the attenuation departs from the normal liquid value; this is in agreement with theory for both phases• The data at 23.17 bar [Figo 1(a)] are similar to those observed by Paulson, Johnson, and Wheatley 3 with the exception of the discontinuity in the velocity and attenuation at the B-A transition, which was not observed in Ref. 3. The data in Fig, 1(b) at 21.80 bars show the situation at a pressure only slightly above the PCP where the A and B transitions are now quite close to each other.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…We have identified the appearance of superfluidity as the temperature where the attenuation departs from the normal liquid value; this is in agreement with theory for both phases• The data at 23.17 bar [Figo 1(a)] are similar to those observed by Paulson, Johnson, and Wheatley 3 with the exception of the discontinuity in the velocity and attenuation at the B-A transition, which was not observed in Ref. 3. The data in Fig, 1(b) at 21.80 bars show the situation at a pressure only slightly above the PCP where the A and B transitions are now quite close to each other.…”
supporting
confidence: 89%
“…1 Earlier studies of sound propagation along the melting curve 2 and at lower pressures 3 showed a large peak in the attenuation at the normal-superfluid transition accompanied by a sharp, but monotonic, decrease in the sound velocity 3 which appeared to extrapolate to the hydrodynamic first-sound value at still lower temperatures. Sound propagation at the B-A transition has not been studied before at pressures between the polycritical point (PCP) and the melting curve; the phase diagram was established by different experimental probes.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…where C x is the velocity of first sound 6 show that p s /p is quite small, varies slowly with temperature, and shows little or no detectable change near the first-order transition at T AB ; this is in possible disagreement with the interpretation of the wire-damping experiments 7 and with a prediction 8 relating 1 -p s /p and zero-sound velocity, but is reasonably close to what one might expect from susceptibility 9 measurements. Our experimental epoxy cell, 2.63 cm long and 2.11 cm in diameter, was packed with cerium magnesium nitrate (CMN) powder (size less than 37 iim) to 80% of crystalline density, the CMN being used as superleak, refrigerant, and thermometer.…”
mentioning
confidence: 48%